Learning and satisfaction levels with online teaching methods among undergraduate dental students - A survey - C Pratheebha; Mahalakshmi Jayaraman (Wolters Kluwer Medknow Publications, 2022)
Taking an online course requires more motivation and self-discipline than taking a classroom-based course. One or more teachers and peers may keep a student responsible for their course work in a classroom. Online classes, on the other hand, enable us to set our own targets, chart our success, and follow deadlines. An awareness-based, self-administered questionnaire was created. The target audience for the study received a link to the questionnaire through Google Docs. The participants were given a thorough explanation of the survey's objectives. Pie charts with a frequency table were created after the survey findings were known. A Chi-square test was used to examine for associations in the statistics, and a P = 0.05 was considered statistically significant. The overall satisfaction level with online classes among students was, 57% were not satisfied with online classes, 31% were satisfied, and 12% were extremely satisfied. Most commonly students were not satisfied with both genders. However, majority of the females were not satisfied. This difference was statistically significant (Pearson's Chi-square value: 1.999, df = 2, P = 0.368 (>0.05) - significant). Eighty percent of the students have faced difficulties while attending online classes. However, 92% of the students have agreed that the technology helped them to attend their online classes.